Comparative study of surface integral methods in aeroacoustic prediction - Xu, Chen; Wang, Shihao; Yang, Dangguo; Zhang, Rongping; Jiang, Shujie; Mao, Yijun (Frontiers in Physics, 2023)
Surface integral methods based on the acoustic analogy and Kirchhoff formulation are widely employed in computational aeroacoustics. The computational accuracy is usually highly dependent on the selections of the acoustic prediction method and of the integral surfaces. This paper analyzes the pros and cons of each aeroacoustic prediction method and studies numerically sound generated from flow past a circular cylinder by employing different surface integral methods. The acoustic analogy based on the impermeable solid surfaces either ignores the quadrupole contribution or needs high computational cost to calculate the quadrupole contribution, and the acoustic analogy based on the permeable integral surfaces usually suffers from the spurious source issue. Both the pressure-based or density-based Kirchhoff formulations can be used in aeroacoustic prediction, however, the numerical results indicate that the pressure-based Kirchhoff formulation also suffers from the issue of the spurious sound because the pressure fluctuations at the permeable integral surfaces are contaminated by hydrodynamic component. It seems that only the density-based Kirchhoff formulation does not suffer from the issue of the spurious sound, but this formulation requires the acoustic sources should be extracted from compressible flow simulations.